2009
DOI: 10.1159/000239767
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Period: Body Composition Changes in Breast-Fed Full-Term Newborns

Abstract: Background: Weight loss during initial days of life in healthy infants is known to consist of loss of both body solids and total body water. However, the nature of these body composition changes needs further investigation. Objective: To investigate the nature of changes in body composition that accompany weight loss during the first days of life in healthy term newborns. Methods: Body composition of healthy full-term newborns was assessed using air-displacement plethysmography. Cross-sectional (n = 262) and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 33 publications
5
28
0
Order By: Relevance
“…Although the magnitude of association was largest for WFAZ, its ability to discriminate between FM and lean mass was only marginally significant; this is likely because weight gain in growing infants and children is nonspecific, as it captures increases in adiposity and the accrual of lean muscle and bone mass (12)(13)(14). When we directly compared how change in %FM, a measure of relative FM that is complementary to percentage lean mass, correlated with change in all 3 indicators at the same time, we found that change in %FM was most strongly associated with change in BMIZ, particularly among AGA and LGA infants.…”
Section: Associations Between Change In Derived Indicators and Adp-mementioning
confidence: 99%
See 2 more Smart Citations
“…Although the magnitude of association was largest for WFAZ, its ability to discriminate between FM and lean mass was only marginally significant; this is likely because weight gain in growing infants and children is nonspecific, as it captures increases in adiposity and the accrual of lean muscle and bone mass (12)(13)(14). When we directly compared how change in %FM, a measure of relative FM that is complementary to percentage lean mass, correlated with change in all 3 indicators at the same time, we found that change in %FM was most strongly associated with change in BMIZ, particularly among AGA and LGA infants.…”
Section: Associations Between Change In Derived Indicators and Adp-mementioning
confidence: 99%
“…Healthy Start comprises a large, multiethnic population of .1000 motherchild pairs, which improves our ability to generalize our findings. In addition, we were able to examine associations of the derived indicators with body composition at .1 time during infancy, which is critical given that the first few postnatal months are characterized by rapid changes in body composition (12)(13)(14). Limitations of this study include the fact that the analysis was restricted to singletons born at term; thus, results may not be applicable to cases of multiple gestation or preterm infants, although we note that a study conducted among preterm neonates found similar results (16).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Full-term newborns were measured on the third day of life (20). Body weight, length, and head circumference were measured according to standard procedures (21).…”
Section: Growth and Body Composition Assessmentmentioning
confidence: 99%
“…Exclusions included neonates with major congenital abnormalities, multiple births, preterm neonates, or admissions to the neonatal intensive care unit for greater than 48 h as illness or invasive monitoring prevented measurement. The greatest loss in BF% occurs on day 3 and therefore to standardize this measurement we included only neonates measured within 48 h of birth (33). The sample size was based on the main study question of estimating the number of neonates with low BF% with a minimum sample size of 384 required to provide a 95% CI ±3%.…”
Section: Subjectsmentioning
confidence: 99%